PENGENDALIAN KECEPATAN MOTOR DC DENGAN METODA FUZZY LOGIC BERBASIS MIKROKONTROLLER - Nasrul Harun (Teknik Elektro Politeknik Negeri Padang, 2009)
The Technology and information development involve production process in industries using microcontroller as a brain in control process. The number of control process with microcontroller using Fuzzy Logic method to get the function as is needed. Motors DC are used in some equipment as a driver, not only in small scale but also in huge scale. It used in low or high speed too. The way of controlled chosen depend on the function of DC motor movement. The another method is Pulse Width Modulation (PWM). This is an effective method to controlled DC motor. This method produces square pulses which have specific comparison between high pulse and low pulse. It is usual scale from 0% to 100%. In this research, both Fuzzy Logic method and Pulse Width Modulation (PWM) method base of microcontroller ATMega 8535, both are integrated to control lthe DC motor speed.